USE OF NATURAL DOLOMITE AS A CHEAP FOAMING AGENT FOR PRODUCING GLASS FOAMS FROM GLASS WASTE IN THE MICROWAVE FIELD - LUCIAN PAUNESCU; MARIUS FLORIN DRAGOESCU; SORIN MIRCEA AXINTE (Journal of Engineering Studies and Research)
The paper presents experimental results obtained in the process of making glass foam from glass waste using a cheap foaming agent (natural dolomite). The originality of the work is the application of the microwave energy, unlike the conventional techniques commonly used in the world. The main advantage highlighted by the experiments is the very low specific energy consumption (below 1.5 kWh/kg), due to the peculiarities of the microwave heating technique. The foamed product has physical, mechanical and morphological characteristics (density between 0.30-0.32 g/cm3, thermal conductivity between 0.064-0.067 W/m·K, compressive strength in the range 2.2-2.6 MPa), which are similar to those of foams made by conventional methods and are suitable for its use as insulating material in construction.